Theory and practice in visual interfaces for semi-structured document discovery and selection - Loizides, Fernando; Buchanan, George R.; Mavri, Aekaterini (My University, 2016)
With the increase in electronic publications, and indeed the availability of existing publications in digital form, as well as the encouragement of open access publication, comes a challenge. That challenge is to create assistive software to aid in the discovery and selection of relevant documents to one's information need. Visual interfaces have begun to address the need of information seekers in finding publications and wading through the large result sets that are returned from search engines. There is currently, little evidence to suggest that these interfaces are based on systematic research on requirements. In this article, we examine areas which contribute to the theory and practice of visual interfaces directly relating to the discovery and selection of publications. We bring together work from different fields in a targeted approach to assist the future creation of these interfaces.
Keywords: Electronic publishing; Information seeking; Interface interaction